Feeding Management Practices Followed by Jaffarabadi Buffalo Owners in Rural Areas of Junagadh District of Gujarat, India - Dodiya, Vivek A.; Sabapara, Ghanshyam P.; Kasondra, Sahil M.; Garg, Deendayal; Odedra, Mulraj D.; Ahlawat, Anshu R. (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
A field study was conducted in Junagadh district of Gujarat to ascertain the housing management practices followed by Jaffarabadi buffalo owners and data were collected from randomly selected 320 respondents through personal interview with the help of structured interview schedule. The study revealed that most (84.06%) of respondents followed stall feeding system for their buffaloes. About 59.38% of buffalo owners fed their buffaloes thrice or more in a day. Majority (75.62%) of respondents provided non-leguminous green fodder and 75.93% respondents fed groundnut gotar as a dry fodder. About 80.31, 84.06 and 91.88% of the respondents fed green and dry fodder as such, fed home-made concentrate feed and not followed scientific criteria for feeding of concentrates, respectively, to their animals. Majority (62.18%) of respondents fed concentrates during milking. About 85.31, 88.12 and 96.88% of buffalo owners fed concentrates to young calves, heifers and advanced pregnant heifers, respectively. Only 23.43 and 26.25% of the respondents provided mineral mixture and salt to their buffaloes. 80.31% of respondents provided water three times in a day in ad libitum quantity.
Keywords: Feeding; Jaffarabadi buffalo; Management; Practices; Rural areas